Investigating the lateral resolution of the Rayleigh wave focal spot imaging technique using two-dimensional acoustic simulations - Giammarinaro, Bruno; Tsarsitalidou, Christina; Hillers, Gregor (Comptes Rendus. Géoscience)
We investigate the lateral resolution power of the seismic Rayleigh wave focal spot imaging technique. We use two-dimensional acoustics simulations in a closed cavity for the passive Green’s function and focal spot reconstruction. Four different velocity distributions target different resolution aspects. The finite data range that is necessary to constrain the Bessel function model controls the lateral spreading of material contrasts, the distinction of two objects on sub-wavelength scales, and the image quality of complex random media. Good data quality from dense networks supports short range estimates and super-resolution.